Asignaciones para el desarrollo : Creación de experiencias de aprendizaje sin cambiar de trabajo - McCauley, Cynthia D. (Cynthia Denise), 1958- (Report (Center for Creative Leadership), 2008)
This book is modeled after "Eighty-Eight Assignments for Development in Place," one of CCL's most popular publications. In the years since that report was published, we have learned more about development in place from research, from working with managers.